Where is the Supervirial Gas? The Supply from Hot Inflows - Manami Roy; Kung-Yi Su; Smita Mathur; Jonathan Stern (The Astrophysical Journal, 2025)
To understand the presence of the supervirial temperature gas detected in the Milky Way (MW), we present our findings from isolated galaxy simulations of MW-mass systems using GIZMO with the Feedback in Realistic Environments (FIRE-2) stellar feedback model. It unveils the presence of a significant supervirial temperature ( T  >  T _vir ) gas component within 20 kpc from the galactic center. We also find that 70%–90% of the total supervirial gas is extraplanar, at 1 <  z  < 6 kpc and R _cyl  < 15 kpc. This supervirial gas has a mass of 1−2 × 10 ^7 M _⊙ with typical gas densities are 10 ^−3.5 −10 ^−2.5 cm ^−3 . We find that some of the virial gas ( T  ∼ 10 ^6 K) forms a rotating hot inflow, where gravitational energy is converted to thermal energy mainly via compressive heating. This process causes gas falling close to the rotation axis to reach supervirial temperatures via a combination of compressive heating and shocks just before cooling and joining the disk. Stellar feedback heating accounts for less than 1% of the supervirial gas, indicating its minimal influence despite expectations. Even in scenarios with no stellar feedback effects considered, abundant supervirial gas persists, highlighting the dominance of alternative heating mechanisms. We also show that cosmic rays do not have a significant effect on heating the gas to a supervirial temperature. Our study illuminates the intricate dynamics of hot virial and supervirial gas surrounding MW-mass galaxies, emphasizing the prominent role of infall-driven compressive and shock-heating processes in shaping thermal evolution.